(untitled) (UNIZIK Journal of STM Education, 2023)
This study was carried out to examine the influence parents and the school has on sport participation of students in secondary schools in Anambra State. Five research questions and hypotheses guided the study. The research anchored on Green’s (2005) Model of Sport Development and Expectancy-Value Theory. The research design used for the study was correlational survey research design. The sample for the study consists of 400 SS1 students in co-educational secondary schools in Anambra State using Taro Yamane formula. Multistage sampling technique was used to select the sample. The instrument used for data collection was questionnaire. Data in this study was analyzed using inferential statistics; Pearson’s Product Moment Correlation (PPMC) was used to answer the research questions, Simple linear regression was used to test hypotheses 1 and 2, hypotheses 3 and 4 was tested using Fisher-Z test while hypotheses 5 was tested using multiple linear regression. The result of the study revealed that there is a significant relationship between parental involvement and sport participation of students in secondary schools in Anambra state. It also revealed that the school can affect sport participation of students in secondary schools in Anambra State. It was therefore concluded that the school and parent influences sport participation among secondary school students in Anambra State. It was recommended that Parents, students, teachers and school administrators should be properly educated on the benefits of sport participation to ones’ mental, psychological and physical wellbeing. School sport programmes should also be encouraged and organized regularly such as inter-house sport competition with the aim of encouraging sport participation and bringing parent, school and the student together.